Deviations from model predictions in measured electron density profiles for low latitudes: A critique - P. Muralikrishna; L. P. Vieira; M. A. Abdu; E. R. de Paula (Geofísica Internacional, 2004)
In situ electron density profiles obtained from equatorial stations in Brazil using conventional Langmuir probes and High Frequency Capacitance probes are compared with IRI predictions in the light of the spectral distribution of the plasma density irregularities observed. Plasma instability mechanisms, especially Rayleigh-Taylor and Cross-Field instability mechanisms responsible for the generation of observed plasma irregularities, are used to estimate the growth time and the minimum scale size of irregularities at different height regions along the electron density profile. Simple polynomial approximations are used to represent the observed electron density profiles. A comparative study of the observed plasma irregularities with those expected from theory can give information on the reliability of the observed profiles. This reliability estimate is important because the techniques used for the measurement of electron density are known to be associated with some problems. Thus one can see whether the deviations of the observed electron density profiles from IRI predictions are genuine, and what are the physical parameters responsible for the observed deviations in the profiles. Some improvements in the methods used for IRI predictions in low latitudes are suggested. doi: https://doi.org/10.22201/igeof.00167169p.2004.43.2.167